Epiphytes provide micro-scale refuge from ocean acidification. (October 2020) - Guy-Haim, Tamar; Silverman, Jacob; Wahl, Martin; Aguirre, Julio; Noisette, Fanny; Rilov, Gil
Abstract: Coralline algae, a major calcifying component of coastal shallow water communities, have been shown to be one of the more vulnerable taxonomic groups to ocean acidification (OA). Under OA, the interaction between corallines and epiphytes was previously described as both positive and negative. We hypothesized that the photosynthetic activity and the complex structure of non-calcifying epiphytic algae that grow on corallines ameliorate the chemical microenvironmental conditions around them, providing protection from OA. Using mesocosm and microsensor experiments, we showed that the widespread coralline Ellisolandia elongata is less susceptible to the detrimental effects of OA when covered with non-calcifying epiphytic algae, and its diffusive boundary layer is thicker than when not covered by epiphytes. By modifying the microenvironmental carbonate chemistry, epiphytes, facilitated by OA, create micro-scale shield (and refuge) with more basic conditions that may allow the persistence of corallines associated with them during acidified conditions. Such ecological refugia could also assist corallines under near-future anthropogenic OA conditions. Highlights: OA induced bleaching and reduced metabolism in non-epiphytized coralline. Epiphytized corallines were less susceptible to the detrimental effects of OA. Epiphytized corallines had thicker diffusive boundary layer than non-epiphytized. Non-calcifying epiphytes provide small scale refuge from OA. Epiphytic refugia may protect corallines under future OA conditions.